Response, Demand, and Control: Evaluating a Three-Factor Model and Measure of Teachers' Interactional Styles. Issue 2 (2nd April 2020) - Torff, Bruce; Kimmons, Kathleen; Budris, Andrew; Solosky, Elizabeth; Maqsood, Jay; Benincasa, Jean; Doeman, Jessica; DePietto, Marilyn; Casamassima, Michael; Walsh, Michelle; Bates, Stephen
Abstract: Theory and research in teachers' interactional styles and authoritative teaching typically posit two factors, including response and a second factor featuring some combination of demand and control . Two survey-research projects examined how teachers construe interactional styles, with results suggesting three discrete factors: response, demand, and control. The optimal interactional style is more complex than the formula of high response and high demand/control emphasized in literature in this area.